Valorization of Agricultural Wastes as Dye Adsorbents: Characterization and Adsorption Isotherms - Contreras-Villacura, E; Sepulveda-Cuevas, L (TAYLOR & FRANCIS LTD, 2015)
The purpose of this work is to evaluate the valorization of agricultural waste, wheat straw (WS) and corn cob leaves (CCLs) as textile dye adsorbents. Physico-chemical and superficial characteristics of the agricultural wastes, together with the interactions with the CI Basic Violet 4 (BV4) dye, were investigated by means of the determination of the isotherm adsorption at different temperatures. The morphological characterization showed that the solid surface is coarse with a low pore level. However, through Fourier transformed infrared analysis, the presence of carboxylic and hydroxylic acid groups and hydrophobic methyl groups was detected. The concentration of acid groups is determined by the Boehm method and was found to be 1.00 and 0.89 meq/g for WS and CCLs, respectively. The point zero charge for each adsorbent was 5.76 and 4.08. Adsorption experimental data presented a better-fit Langmuir model, indicating that adsorption occurred in a monolayer with preferential interaction. The maximum adsorption capacity was determined to be 70.0-89.0 and 47.0-68.0 mg/g for CCLs and WS, respectively. The thermodynamic analysis of the Langmuir parameter b showed that the adsorption of the BV4 dye is spontaneous and exothermic with adsorption energies of 14.43 and 5.58 KJ/mol for CCLs and WS, respectively.